Subtitled Films and Learning Listening Comprehension: A Study in Bulukumba, Indonesia - Anugrah Febrian Syam; Andi Qashas Rahman (ELT Worldwide: Journal of English Language Teaching, 2014)
This present study is aimed at finding out (1) the possible effect of subtitled and non-subtitled movies on students’ listening achievement, and (2) the difference between using subtitled and non-subtitled movies in students’ listening comprehension. A Comparative study using two groups with a pre-test and post-test design was undertaken in this research. The data were collected using the IELTS listening test. There were two results in the data analysis of IELTS listening test. The first, a general improvement was noted. It was found that both procedures (presenting the movie with or without subtitles) produced a positive effect. Second, the result of movie task data analysis indicated a positive effect for both groups; both groups significantly improved during six weeks. It was revealed that subtitled group exercised a better performance than non-subtitled group. Keywords: Subtitled movies, Non-subtitled movies, The IELTS Listening Test.